In Search of New Clasifications (Devision into Periods Methodology Problems in Russian Literature) - Serdiuchenko, V. (Literatūra, 1975)
The article enters into polemics with V. Kozhinov, who denies the traditional division into periods principle in Russian literature.
Keywords: -